KEKUATAN PEMBUKTIAN AKTA DIBAWAH TANGAN YANG DILEGALISASI NOTARIS DENPASAR - Aga Septian Prawira, Made; Ari Atu Dewi, A. A. Istri (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 05, Juli 2013, 2013)
A paper entitled "Proof of Deed Under Power Hand Notary Denpasarlegalized" aims to To know and understand about the strength of evidence under theDeed of hands that have been validated by a notary, particularly in Denpasar. Thiswriting method using the Juridical Empirical research methods. Deed under the handstrength of evidence that legalized notary deed is not the same as authentic as it canstill be denied the truth and the truth shall prove through other evidence or witnesses.Notarial deed dated ensures certainty and signatures of the parties, but is notresponsible for the contents of the deed.
Keywords: Evidence, the Deed Under Hand, Legalization